The nanny's Amish family - Johns, Patricia (Romance writer) (Johns, Patricia. Redemption's Amish Legacies., 2020)
"Schoolteacher Patience Flaud longs for a family of her own- but knows it can never happen. At least she can help Amish bachelor Thomas Wiebe with his small Englisher daughter. As she settles the child into Amish life, Patience begins falling for the bewildered new father and his heartbroken little girl. But is love enough to make them a permanent family?" --